Comparison of “Mucopexy with Haemorrhoidal Artery Ligation with Open Hemorrhoidectomy in Terms of Effectiveness and Outcome: Mucopexy with Haemorrhoidal Artery Ligation with Open Hemorrhoidectomy - Asad, Muhammad; Rehman, Kiran; Seerat, Muhammad Ismail; Iftikhar, Maryam; Ahmed, Bilal; Hameed, Adil; Rauf, Sufyan (Pakistan Journal of Health Sciences, 2025)
Traditional haemorrhoidectomy techniques are effective in the treatment of haemorrhoids but are associated with an increased risk of postoperative bleeding, pain, and longer recovery time. Our study on Mucopexy with haemorrhoidal artery ligation compares the outcomes in both procedures. Objective: To compare operating time, postoperative pain and bleeding, and postoperative urinary retention with both methods. Methods: This randomized control trial was conducted at the Department of General Surgery at the Pakistan Railway Hospital from January 2023 to December 2023. Results: In the hemorrhoidectomy group, the median age was 44.6 ± 14.54 years and the mean age of 50.91 ± 17.23 years for the other group. The mean operating time for the Hemorrhoidectomy group was 56.04 ± 7.52 minutes, while for the Mucopexy group, it was 40.36 ± 6.85 minutes. The difference was significant (p=0.000000000000000078). On the 1st day, the mean pain score (numerical rating scale for pain) for the Hemorrhoidectomy group was 7.00 ± 1.17, whereas for the Mucopexy group, it was 3.59 ± 1.15 with a significant difference (p=0.000000000000000578). On the 7th postoperative day, the mean score on the numerical rating scale for pain for the Hemorrhoidectomy group was 2.37 ± 1.10, as compared to the mucopexy group, which was 1.07 ± 0.25, (p=0.0000000000258). No statistically significant difference was found for Postoperative bleeding and urinary retention between the two groups. Conclusions: It was concluded that HAL with Mucopexy has shown significant improvement in postoperative pain and operating time as compared to the open haemorrhoidectomy.